Predictors of Major Bleeding and Mortality in Dengue Infection: A Retrospective Observational Study in a Tertiary Care Centre in South India. (4th September 2019) - John, Kevin John; Gunasekaran, Karthik; Prasad, John Davis; Mathew, Divya; Das, Sohini; Sultan, N.; Abraham, Asha Mary; Iyyadurai, Ramya
Abstract : We conducted a retrospective observational study to describe the clinical profile and outcomes of patients admitted with a diagnosis of dengue fever in a tertiary hospital in South India. A total of 159 patients admitted from April 2014 to October 2018 were included in the study. Vomiting (70.4%), myalgia (60.4%), headache (42.1%), abdominal pain (38.4%), bleeding (38%), and rash (37.1%) were the most common symptoms at presentation. The mean duration of hospital stay was 4.9 days (SD ± 2.4), and the median cost was INR 19, 708 (285) (IQR INR 12, 968–32, 056 (188–305)). Major bleeding was associated with elevated SGOT and SGPT, severe dengue, and secondary dengue. Mortality was associated with elderly age; elevated total leukocyte count, serum bilirubin, serum creatinine, SGOT, and SGPT; and high SOFA score. In view of these observations, we recommend stratifying patients according to the WHO classification of dengue and avoiding the use of thrombocytopenia as a single marker of the severity of the illness.